Incentives and Their Impact on Employee Satisfaction - Iskamto, Dedi; Santosa, Budi; Juhariyah, Lohana; Ghazali, Puspa Liza (International Journal of Entrepreneurship and Business Management, 2024)
This study aims to examine the influence of Financial Incentives, Non-Financial Incentives, and Employee Performance variables on Employee Job Satisfaction. This study uses a quantitative method where a questionnaire is used to obtain primary data, for samples taken from a private company, using simple random sampling, for data processing and hypothesis testing using SPSS version 23. It was found that it was concluded that Financial Incentives affect Employee Job Satisfaction. Non-Financial Incentives do not affect Employee Job Satisfaction. Employee Performance affects Employee Job Satisfaction. shows that Financial Incentives, Non-Financial Incentives, Employee Performance simultaneously affect Employee Job Satisfaction